The Reflective and Impulsive Graduate Student’s Creativity Problem Solving of Three Variables of Linear Equations System - Demitra Demitra; Sarjoko Sarjoko; Desti Haryani; Maulida Yunita; Leyli Yustarina Pebriani (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
The challenge for prospective mathematics teachers in the future is to have a good mastery of the material, be able to solve math problems and think creatively. So that later they will be able to guide their students to develop creativity in 21st-century life. Cognitive style and learning influence the establishment of the creativity of mathematical problem-solving. The purpose of the study was to describe the creativity of students with reflective and impulsive cognitive styles in solving problems of a three-variable linear equation system. The research was carried out using descriptive-qualitative research methods. The research subjects were the Mathematics Education Study Program students at the University of Palangka Raya. The research instrument uses the Matching Familiar Figure Test, a problem-solving ability test, and an analytic rubric. Data were analyzed by scatterplot, pie diagram, reduction, triangulation, and inference. Research findings on students with reflective cognitive style in stages (1) understand problems and develop mathematical models with fluency, flexibility, originality, and elaboration; (2) complete the plan with fluency, flexibility, and elaboration; (3) check the results with fluency and elaboration. Students with impulsive cognitive styles are only in the stage of understanding the problem with fluency, novelty, and elaboration indicators.Tantangan bagi calon guru matematika di masa depan harus menguasai materi, mampu memecahkan masalah matematika dan kreativitas berpikir yang baik. Agar nantinya mereka mampu membimbing para siswanya mengembangkan kreativitas dalam kehidupan abad 21. Gaya kognitif dan pembelajaran berpengaruh terhadap pembentukan kreativitas memecahkan masalah matematika. Tujuan penelitian mendeskripsikan kreativitas mahasiswa dengan gaya kognitif reflektif dan impulsif memecahkan masalah sistem persamaan linier tiga variabel, Penelitian dilaksanakan dengan metode penelitian deskriptif-kualitatif. Subjek penelitian adalah mahasiswa Program Studi Pendidikan Matematika Universitas Palangka Raya. Instrumen penelitian menggunakan Matching Familiar Figure Test, tes kemampuan pemecahan masalah dan rubrik analitik. Data dianalisis dengan scatterplot dan pie diagram, reduksi, triangulasi dan penyimpulan. Temuan penelitian pada mahasiswa dengan gaya kognitif reflektif pada tahap-tahap (1) memahami masalah dan menyusun model matematika dengan kefasihan, keluwesan, kebaharuan, dan elaborasi; (2) menyelesaikan rencana dengan fasihan, keluwesan, dan elaborasi; (3) memeriksa hasil dengan kefasihan dan elaborasi. Mahasiswa dengan gaya kognitif impulsif hanya tahap memahami masalah dengan indikator kefasihan, kebaharuan, dan elaborasi.